Enhancing end-of-life care for terminally ill psychiatric patients. Issue 8 (August 2016) - Steves, Faith; Williams, Tommy
Abstract : Find out how nurses caring for these patients can battle the stigma of mental illness and improve access to quality end-of-life care.